Nurses’ experiences in caring for dying patients: A literature review - Agus Ari Pratama; Shanti Wardaningsih (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Every human will face death, and some patients can experience a critical condition during illness before death. Nurses are medical professionals who are expected to be able to care for a patient's critical condition. Studying experiences of nurses in dealing with a patient's critical condition is needed so that they can improve their services. This study aims to analyze articles that explain about nurses' experiences in dealing with dying patients. A literature review was conducted by searching articles from the PubMed and EBSCO databases (using keywords